2004
DOI: 10.1093/alcalc/agh041
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Brain Function Between Relapsing and Abstaining Alcohol-Dependent Patients, Evaluated by Eeg Mapping

Abstract: EEG maps of alcohol-dependent patients differ significantly from those of normal controls and patients suffering from other mental disorders and thus EEG mapping may be used for diagnostic purposes. Moreover, the quantitative EEG may also be of prognostic value as relapsing patients differ from abstaining ones, since they show a significantly more pronounced hyperarousal of the CNS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 54 publications
6
97
0
2
Order By: Relevance
“…Using the resting EEG for diagnostic and preventive purposes, therefore, makes sense. Moreover, EEGs may also be of prognostic value, as EEG patterns in patients who relapse differ from those in patients who continue to abstain [147]. In summary, as slow theta activity is believed to be inhibitory, alpha activity to reflect normal brain functioning, and fast beta activity to be excitatory, the low-voltage fast desynchronized patterns described in alcoholics may reflect hyperarousal of the CNS.…”
Section: Beta Bandmentioning
confidence: 99%
“…Using the resting EEG for diagnostic and preventive purposes, therefore, makes sense. Moreover, EEGs may also be of prognostic value, as EEG patterns in patients who relapse differ from those in patients who continue to abstain [147]. In summary, as slow theta activity is believed to be inhibitory, alpha activity to reflect normal brain functioning, and fast beta activity to be excitatory, the low-voltage fast desynchronized patterns described in alcoholics may reflect hyperarousal of the CNS.…”
Section: Beta Bandmentioning
confidence: 99%
“…As slow activities are considered to be inhibitory, alpha activity may be viewed as an expression of normal brain functioning and fast beta activities as excitatory, the lowvoltage fast desynchronized patterns may be interpreted as hyperarousal of the central nervous system (CNS) (Saletu-Zyhlarz et al, 2004). The investigations by Bauer (2001b) and Winterer et al (1998) showed a worse prognosis for the patient group with a more 8 JOURNAL OF NEUROTHERAPY pronounced frontal CNS hyperarousal.…”
Section: Qeeg In Sudmentioning
confidence: 99%
“…It may be hypothesized that these hyperaroused relapsing patients require more CNS sedation than abstaining ones. EEG maps of alcohol-dependent patients differ significantly from those of normal controls and patients suffering from other mental disorders and might be useful for diagnostic purposes (Pollock, Schneider, Zemansky, Gleason, & Pawluczyk, 1992;Saletu et al, 2002;Saletu-Zyhlarz et al, 2004). Decreased power in slow bands in alcoholic patients may be an indicator of brain atrophy and chronic brain damage, whereas an increase in the beta band may be related to various factors such as medication use, family history of alcoholism, and=or hallucinations, suggesting a state of cortical hyperexcitability (CoutinChurchman, Moreno, Añ nez, & Vergara, 2006).…”
Section: Qeeg In Sudmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol-dependent individuals have different synchronization of brain activity than light drinkers as reflected by differences in resting EEG coherence (Kaplan et al, 1985;Michael et al, 1993;Winterer et al, 2003a) and power (e.g., Bauer, 2001;Enoch et al, 2002;Rangaswamy et al, 2002;Saletu-Zyhlarz et al, 2004). Most differences in EEG coherence and power are found at alpha (8-12 Hz), slowbeta (12 -20 Hz), and fast-beta (20 -30 Hz) frequencies.…”
Section: Introductionmentioning
confidence: 99%